Medial Parabrachial Nucleus Is Essential in Controlling Wakefulness in Rats - Xu, Qi; Wang, Dian-Ru; Dong, Hui; Chen, Li; Lu, Jun; Lazarus, Michael; Cherasse, Yoan; Chen, Gui-Hai; Qu, Wei-Min; Huang, Zhi-Li (Frontiers in Neuroscience, 2021)
Activate the parabrachial nucleus (PB) in the brainstem induced wakefulness in rats, suggesting which is an important nucleus that controls arousal. However, the sub-regions of PB in regulating sleep-wake cycle is still unclear. Here, we employ the chemogenetics and optogenetics strategies and find that activation of the medial part of PB (MPB), but not the lateral part, induces continuous wakefulness for 10 h without sleep rebound in neither sleep amount nor the power spectra. Optogenetic activation of glutamatergic MPB neurons in sleeping rats immediately wake rats mediated by the basal forebrain (BF) and lateral hypothalamus (LH), but not the ventral medial of thalamus. Most importantly, chemogenetic inhibition of PB neurons decreases wakefulness for 10 h. Conclusively, these findings indicate that the glutamatergic MPB neurons are essential in controlling wakefulness, and that MPB-BF and MPB-LH pathways are the major neuronal circuits.